Suicidal incidence and gender-based discrepancies in prolonged grief disorder: insights from a meta-analysis and systematic review - Tu, Jin-Heng; Lu, Yun; Yue, Zong-Chao; Ling, Ke-Nan; Xing, Yu-Run; Chen, Dan-Dan; Zhu, Zhi-Ren; Chen, Tian-Xi (Frontiers in Psychiatry, 2024)
Background: In the aftermath of bereavement, our research explores the subtleties of Prolonged Grief Disorder (PGD), focusing particularly on its correlation with suicidal behaviors and their variation across genders. This study seeks to elucidate the impact of gender on these behaviors among individuals suffering from PGD, thereby enhancing our understanding and facilitating the development of tailored therapeutic interventions.Methods: By November 24th, 2023, we had rigorously reviewed key databases such as PubMed, Web of Science, Cochrane Library, PsycINFO, and Embase. Independently, two researchers conducted detailed interviews and filled out questionnaires with participants to gather demographic information and record instances of prolonged grief disorder. The study also meticulously tracked occurrences of suicidal ideation, suicide attempts, suicide deaths, and self-injury among the participants.Results: The findings indicate that 22.34% of males reported suicidal ideation (95% CI: 21.33-23.35), a figure that rises to 26.84% among females (95% CI: 25.99-27.69). Notably, 12.11% of males attempted suicide (95% CI: 11.49-12.72), marginally surpassing the 9.60% observed in females (95% CI: 9.17-10.04). More striking disparities were observed in suicide deaths, with rates for males at 3.66% (95% CI: 3.32-4.00) compared to a notably higher 7.12% for females (95% CI: 6.44-7.81).Furthermore, the incidence of self-injury was lower among males, at 2.48% (95% CI: 2.03-2.94), than 2 in females, who reported a rate of 5.09% (95% CI: 4.69-5.49). These patterns underscore the critical need for gender-specific interventions aimed at reducing these significant disparities.Conclusions: This study distinctly underscores the profound impact of gender on the manifestation of suicidal behaviors in individuals afflicted with prolonged grief disorder. It reveals that females are more prone to suicidal ideation, self-injury, and suicide deaths, while males predominantly exhibit a higher incidence of suicide attempts and risk-taking behaviors. These unmediated trends highlight the necessity for gender-specific clinical interventions tailored to address particular behaviors and modify prevalent patterns that typically resist conventional approaches.Systematic review registration: This study sign up for PROSPERO, ( PROSPERO (york.ac.uk))， identifier CRD42023480035.